Correlation of Depth of Anesthesia with Hemodynamic Parameters in Patients Undergoing Elective Abdominal Surgery - Khadijeh Yazdi; Arazbordi Ghorchaei; Shakiba Mozari; Fariba Baghani; Ali Akbar Abdollahy; Naser Behnampour (Golestan University of Medical Sciences, 2015)
Background and Objective: The usual method of assessing depth of anesthesia, which is not sensitive and specific enough, is measuring hemodynamic parameters, autonomic changes and subjective symptoms including movement, sweating and lacrimation. This study aimed to determine the relationship between the depth of anesthesia and hemodynamic indices. Material and Methods: This correlational study was conducted on 57 patients undergoing elective hernia surgery in Shahid Beheshti Hospital ,Sabzevar in summer 2014.  An identical anesthesia technique was used for all patients.  Depth of anesthesia was monitored quantitatively by bispectral index (BIS) at 5-minute intervals, with simultaneous recording of heart rate and blood pressure. We analyzed the data using Anova and correlation coefficient. Results: The mean age was 45.54±13.46. The patients were males (n=36) and females (n= 21).   Only 59.6 % of the patients experienced a normal depth of anesthesia. Hemodynamic parameters were not significantly correlated with anesthetic depth except for heart rate in the first 5 minutes (P= 0.013). Conclusion: Given that hemodynamic parameters have some limitations in determining the acceptable depth of anesthesia, we recommend using the monitors based on brain signal processing.